Language Study in Irwan Prayitno's Pantun (Governor of Sumatera Barat) - Jaya Nasa Perta; Ermanto Ermanto (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2020)
The purpose of this study is to look at the language (diction) used and pantun in pantun in the speech of Irwan Prayitno (Governor of Sumatera Barat).  The data of this study are words in the poem with the source of spontaneous pantun data collection ala Irwan Prayitno. This research describes pantun (identification and classification) based on word types.  Based on the research objectives, the findings of this study are as follows. First the language study, the choice of words that are often found are the name of a person, the name of a place or region, and the name of a profession or nickname.  The two pantun structures, the poetry found in general, ab.ab., then aa.aa, ab.aa, and ab.bb. By analyzing and linking the diction used, the findings of this study say the rhymes in Irwan Prayitno's speech (Governor of Sumatera Barat) have specific spontaneity as evidenced by the diction used that is relevant to the situation or condition of the speech event that took place.